(3GdGJLGgGJ GdfbOjI aj GdEYdGe hGdGJUGd (B: s (3eWHhYI ebOeI dWdHI GdSfI GdKGfjI eGSJQ (B/ s - (3Hf YeQhT, aQjOIs; (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs ((3GdLRGFQs (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs, 2019)
(3GdfXQjI GdfbOjI(B: (3GdCSS GdfXQjI,GdeOQSI GdfbOjI GdHQjWGfjI,GdeOQSI GdfbOjI GdCeQjcjI,fXQjGJ GdJMce HGdLeGgjQ,NUGFU LeghQ hSGFd GdEYdGe hCfhGY GdJdbj,hSGFd GdGJUGd hGdeLJeY GdeYGUQ,GdEjOjhdhLjI hGdeLJeY GdTHcj,OjebQGWjI GdEYdGe hGdGJUGd,GdYhdeI GdEYdGejI(B.s
(3GdeQGLY U(B.187s
Keywords: (3GdGJUGds; (3GdGYdGes